(untitled) (Modern Information Technologies and Innovation Methodologies of Education in Professional Training Methodology Theory Experience Problems, 2016)
The most urgent issue of foreign language training of students in terms of socio-economic dynamic transformationof Ukraine and integration of our country into the world educational space is considered. From the standpoint of current theoretical andmethodological fundamentals the comprehensive description of the impact of innovative pedagogical and information communicationtechnology upon the effectiveness and result of foreign language learning is provided. The objective analysis of the best internationalpractices, including the US, allows national educational community effectively address organizational, teaching, technical andmanagerial problems about the ICT usage in the educational process of higher education, is proved. Peculiarities of digital storytellingusage in the foreign language learning in the higher education system in the context of leading American universities are defined. Anumber of positive points about the application of technology of interactive digital storytelling when learning a foreign language inhigher education (improved students' motivation, increased confidence in foreign language learning, a situation of success creation,promotion of better understanding of material, etc.) and a number of difficulties regarding innovative technology use in the nationaleducational practice is determined. The particular attention to critical thinking and creative use of foreign experience in foreign languagetraining of future specialists in Ukraine is paid.